Flexible piezoresistive pressure sensor based on wrinkled layers with fast response for wearable applications. (30th September 2022) - Du, Dawei; Ma, Xinyue; An, Wenxing; Yu, Shihui
Highlights: A high-sensitivity flexible piezoresistive sensor is developed by placing two layers of silver nanowires (AgNWs) coated polydimethylsiloxane (PDMS) in a wrinkled structure. The sensor presents a very fast response time (10 ms). The sensor shows a very low pressure detection limit (<1 Pa). The sensor is successfully used to detect the real-time pressure change of muscle movement and recognize vocalizations. Abstract: Flexible piezoresistive sensors are promising candidates for vital components of prospective wearable sensing systems in human-centered intelligent applications. Herein, we present a novel flexible piezoresistive pressure sensor based on the structure of silver nanowires (AgNWs) on polydimethylsiloxane (PDMS) with a wrinkled surface. Modifying the PDMS microstructure enables the sensor to obtain different sensitivities and pressure ranges. At the optimal conditions, our sensor exhibits a high sensitivity of 2.588 kPa −1 and a large pressure range with a very low detectable pressure limit (<1 Pa), which can measure a seed weight of sesame (∼2 mg). Furthermore, The elastic microstructure-based piezoresistive sensor also possesses a very fast response time (10 ms), rapid recovery (20 ms), and excellent cycling stability. The real-time pressure detection ability is demonstrated by the touching behavior, the muscle and joint movement and the vocalization recognition, presenting great application potential in human–machine interaction, human motion monitoring and intelligent robotic systems.